Microcirculation Approach in HELLP Syndrome Complicated by Posterior Reversible Encephalopathy Syndrome and Massive Hepatic Infarction. (17th November 2014) - Sarmento, Stephanno Gomes Pereira; Santana, Eduardo Feliz Martins; Campanharo, Felipe Favorette; Araujo Júnior, Edward; Machado, Flavia Ribeiro; Sass, Nelson; Moron, Antonio Fernandes
Abstract : HELLP syndrome is a complication of severe forms of preeclampsia and occurs mainly in the third trimester of pregnancy. In extreme cases, it may evolve unfavorably and substantially increase maternal mortality. We present the case of an 18-year-old pregnant woman who was admitted to our emergency service in her 31st week, presenting with headache, visual disturbances, and epigastralgia, with progression to a severe condition of HELLP syndrome followed by posterior reversible encephalopathy syndrome (PRES) and hepatic infarction. We highlight the approach taken towards this patient and the case management, in which, in addition to the imaging examinations routinely available, we also used the sidestream dark field (SDF) technique to evaluate the systemic microcirculation.